Pengaruh Disiplin Kerja Terhadap Produktivitas Pegawai (suatu studi di Kantor Kelurahan Tingkulu Kecamatan Wanea Kota Manado) - Ruauw, Astria; Lengkong, florence Daicy; Mandey, Jantje (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT Labor discipline is a behavioral containing technical aspects that work ethic is the norms that are binding and are set explicitly and practices such as behavioral attitudes respect, honor, obey, and obey that must be held to be maintained and implemented in government agencies. Problems to be answered in this study is the work discipline of employees about employee performance affects the productivity of employees working in the Village Tingkulu Wanea districts of Manado. This study aims to determine the effect of labor discipline against the employee productivity. These results indicate that the labor discipline and significant positive effect on the productivity of employees in the Village Tingkulu Wanea District of Manado City. Based on these conclusions labor discipline must be observed and maintained on each employee so that the tasks and responsibilities can be a priority terselenggarakan well. Keywords: influence, discipline, performance, employee productivity